ANALISA KESESUAIAN UNSUR PENYAJIAN PETA KELURAHAN PANYURAN BERDASARKAN PERKA BIG NO. 3 TAHUN 2016 - Rofita, Ziyadatul; Sukojo , Bangun Muljo; Deviantari , Udiana Wahyu (Geoid, 2019)
Village map is a basic thematic map that contains elements and information on boundaries, transportation infrastructure, toponyms, waters, infrastructure, land cover and land use that are presented in several map forms. The diversity of village map types in Indonesia is one of the reasons for the Geospatial Information Agency to make a standardization policy of village mapping as a national reference. Procurement of village maps is needed to accelerate the process of village and rural development by utilizing spatial data. The final result of this study is a village map consisting of an image map, a map of land cover, and a map of infrastructure. The presentation of the Panyuran Sub-District map is adjusted to the map elements that must be displayed in accordance with BIG Decree No. 3 of 2016. The percentage of conformity of the presentation of image maps to the mandatory elements is 71.43%, 0% selected elements, and conditional elements 91.30%. Then the percentage of suitability of the presentation of the map of land cover to the mandatory elements is 71.43%, the optional element is 0%, and the conditional element is 88.89%. While the percentage of suitability of the presentation of infrastructure map is 75.00% mandatory element, 0% optional element, and 92.00% conditional element.